STRATEGI KOMUNIKASI POLITIK PASANGAN SYAMSUAR DAN ALFEDRI DALAM PEMILIHAN UMUM KEPALA DAERAH KABUPATEN SIAK PERIODE 2015 - 2020 - harijummaulana maulana (JURNAL PURNAMA BERAZAM, 2020)
Regencial general election was a political event occurred in entire Indonesia’s territories. The restriction of time availability provided by General Election Commission (KPU) drove the candidates along with their compaign team to construct effective strategy for political communication due to embrace whole community stratum on electoral areas. Siak Regency was one of Riau provincialregion, which established general election on December 9th, 2015 for which two prominent candidates eagerly participated, namely; Suhartono-Syahrul partner or (BERKAH) and Syamsuar-Alfedri partner or (SUARA) as incumbent candidates. The research purpose primarily addressed to decribe the strategy of political communication by Syamsuar-Alfedri partner or (SUARA) to gain winning at Regencial General Election for Head and Vice Regency of Siak for 2015 to 2020 services. The research methodology was descriptive qualitative. Data collection technique comprised consecutively of interview, observation and documentation. Its primary data composed of a depth interview with reliable sourcers. The research variable was the strategy of political communication with the indicators as of followed: (a) politic communicators; (b) political massages; (c) political media; (d) political targetting; and (e) political communication effects. Based on the research findings through qualitative analysis, it was eventually found that: (a) the political communicators for Syamsuar-Alfedri partner consisted of Syamsuar, Alfedri, Bappedal, Head of District, head of adminsitrative depertements and chiefs of sommunities; (b) political massages by Syamsuar-Alfedri partner were “suara”, “lanjutkan” and “suai” (voice, move on and matching); (c) political media by Syamsuar-Alfedri partner were offline media, printed media, social media and social networking; (d) political targettings by Syamsuar-Alfedri partner were entire communities stratum and youth of initial voters; and (e) political communication effects by Syamsuar-Alfedri partner were massive amount of communities actively joined voting and Syamsuar-Alfedri partner evidently won significantly voting account in Siak regencial general Election.